195k views
0 votes
Substitution
x+2y=3
-3x+4y=-4

User Shaun
by
7.0k points

2 Answers

7 votes
x + 2y = 3.........(i)
-3x + 4y = -4.....(ii)

From the first equation, x = 3 - 2y ......(iii)
Substituting equation (iii) into equation (ii)

-3x + 4y = -4.....(ii)
-3(3 - 2y) + 4y = -4
-9 + 6y + 4y = -4
-9 + 10y = -4
10y = -4 +9
10y = 5 Divide both sides by 10
y = 5/10
y = 0.5

Substituting y = 0.5 into x = 3 - 2y ......(iii)
x = 3 - 2y
x = 3 - 2(0.5) = 3 - 1= 2.

x = 2, y = 0.5
User Angelica Rosa
by
8.6k points
6 votes
x+2y=3 -3x+4y=-4
x + 2y = 3
- 2y -2y

x = 3 - 2y
-3(3-2y) + 2y = -4

-9 + 6y + 2y = -4
-9 + 8y = -4
+9 +9
8y = 5
y = 0.625


-3x+4y=-4
-3x + 4(0.625) = -4
-3x + 2.5 = -4
-3x = -6.5
x = 2.16

x = 2.16
y = 0.625
User James Coyle
by
7.5k points

No related questions found